2021
DOI: 10.3390/ijerph18042168
|View full text |Cite
|
Sign up to set email alerts
|

Pavement Overrides the Effects of Tree Species on Soil Bacterial Communities

Abstract: Human disturbance and vegetation are known to affect soil microorganisms. However, the interacting effects of pavement and plant species on soil bacterial communities have received far less attention. In this study, we collected soil samples from pine (Pinus tabuliformis Carr.), ash (Fraxinus chinensis), and maple (Acer truncatum Bunge) stands that grew in impervious, pervious, and no pavement blocks to investigate the way pavement, tree species, and their interaction influence soil bacterial communities by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For example, the Fagus grandifolia (beech) rhizomicrobiota showed greater sensitivity to urbanization pressure compared to the Liriodendron tulipifera (yellow poplar) microbial community. Similarly, paving seemed to have a greater effect on Pinus tabuliformis (pine) root bacterial communities than on the Fraxinus chinensis (ash) and Acer truncatum (maple) communities [105,106].…”
Section: Rhodococcus Rhodococcus Representativesmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, the Fagus grandifolia (beech) rhizomicrobiota showed greater sensitivity to urbanization pressure compared to the Liriodendron tulipifera (yellow poplar) microbial community. Similarly, paving seemed to have a greater effect on Pinus tabuliformis (pine) root bacterial communities than on the Fraxinus chinensis (ash) and Acer truncatum (maple) communities [105,106].…”
Section: Rhodococcus Rhodococcus Representativesmentioning
confidence: 98%
“…The examination of these works revealed that plants in urban contexts, as in natural environments, exerted an important influence on the rhizosphere microbial communities and affected their structure and composition via the modulation of soil chemistry (Figure 4) [95,[104][105][106][107]. For example, plants played a role in modifying the rhizosphere pH via different root-mediated processes.…”
Section: Factors Influencing the Urban Soil (Rhizo)microbiotamentioning
confidence: 99%
See 1 more Smart Citation